Evropska shema za trgovanje z emisijami in njeni učinki na poslovanje podjetij - Czerny, Albert (Naše gospodarstvo, 2010)
The European Emissions Trading Scheme (EU ETS), which serves as a cornerstone of the European Union''s climate policy, started operating in 2005. In order to investigate the effects of EU ETS on companies, five case studies of Slovenian companies were conducted. According to the findings, the studied companies are very familiar with EU ETS. They have all traded with emission allowances, primarily buying them to make up for the shortfall in allowances. The introduction of EU ETS provided a stimulus for actual emission reductions as all companies have taken actions to reduce emissions. The main problem of EU ETS in their view is that it bears additional costs and, therefore, represents a cost disadvantage relative to companies from third countries, where such schemes do not exist.
Keywords: European Union; Evropska unija; okoljevarstvena politika; podjetja; onesnaževanje; emisija; preprečevanje; emisijska dovoljenja; trade; trgovina